Elevated expression of JAM‐A promotes neoplastic properties of lung adenocarcinoma. Issue 11 (18th September 2017) - Magara, Kazufumi; Takasawa, Akira; Osanai, Makoto; Ota, Misaki; Tagami, Yohei; Ono, Yusuke; Takasawa, Kumi; Murata, Masaki; Hirohashi, Yoshihiko; Miyajima, Masahiro; Yamada, Gen; Hasegawa, Tadashi; et al.
Abstract : A cell–cell adhesion protein, junctional adhesion molecule‐A (JAM‐A), has been shown to be involved in neoplasia of various organs. However, the fundamental role of JAM‐A in tumorigenesis is still under debate because dysregulated expression of this protein has distinct effects, playing opposite roles in carcinogenesis depending on the target tissues. In the present study, we found elevated levels of JAM‐A expression in lung adenocarcinoma and its preinvasive lesions, including atypical adenomatous hyperplasia and adenocarcinoma in situ by immunohistochemistry. We also showed that suppression of constitutive JAM‐A expression conferred target cells with increased susceptibility to apoptosis in lung adenocarcinoma cells. Consequently, inhibition of JAM‐A activity decreased colony‐forming capability in vitro and tumorigenicity in vivo . The transformed phenotype following suppression of JAM‐A expression was sufficient to reduce motile and invasive capacities. Importantly, knockout of JAM‐A had striking effects on cells. Our observations suggest that increased expression of JAM‐A promotes neoplasia of lung adenocarcinoma. In addition, an anti‐JAM‐A antibody efficiently reduced cell proliferation and provoked apoptosis, indicating the potential feasibility of JAM‐A‐inhibitory cancer therapy. Abstract : Immunohistochemical analyses showed elevated levels of JAM‐A expression in lung adenocarcinomas, including acinar, papillary, and solid types, and its preinvasive lesions, including atypical adenomatous hyperplasia and adenocarcinoma in situ . The present study suggested that increased expression of JAM‐A promotes neoplasia of lung adenocarcinoma, indicating the potential feasibility of JAM‐A‐inhibitory cancer therapy.